Pig surgery: cryptorchidectomy using an inguinal approach. (11th June 2016) - Scollo, A.; Martelli, P.; Borri, E.; Mazzoni, C.
Abstract : The objective of the study was to determine whether a less‐invasive surgical technique used in cryptorchid horses, dogs and cats can be used successfully to remove retained testicles in pigs on farm. In total, 284 monolateral cryptorchid pigs underwent surgery on‐farm condition, during which an incision was made over the inguinal ring and the undescended testicle was located for removal via identification of the vaginal process and the embryonic gubernaculum. A traction of these structures allowed the testis to pass through the deep and the superficial rings up to its exteriorisation outside the abdominal wall through the inguinal canal. The undescended testicle was located in the abdomen in 258 cases (90.8 per cent) and in the inguinal region in the remaining 26 cases (9.1 per cent). In none of the pigs was the abdominal cavity breached or the inguinal rings enlarged. However, in 23 pigs (8.1 per cent) the gubernaculum testis was thin and it frayed and ruptured when traction was applied, requiring a recovering by inserting a finger and Kelly curved forceps into the abdomen through the inguinal ring. In two pigs (0.7 per cent), the undescended testicle was not found. All surgical procedures were completed within 6–12 minutes. Four pigs died within two days after surgery (1.4 per cent). Major intraoperative or long‐term complications did not occur. Results suggested that this surgical method is highly effective and could be used as a primary surgical approach in cryptorchid pigs as it is in cryptorchid dogs, cats and horses.